2018
DOI: 10.1186/s13569-018-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of whole exome sequencing and murine patient derived xenografts as a method of chemosensitivity testing in sarcoma

Abstract: BackgroundSoft tissue and bone sarcoma represent a broad spectrum of different pathology and genetic variance. Current chemotherapy regimens are derived from randomised trials and represent empirical treatment. Chemosensitivity testing and whole exome sequencing (WES) may offer personalized chemotherapy treatment based on genetic mutations.MethodsA pilot, prospective, non-randomised control experimental study was conducted. Twelve patients with metastatic bone or soft tissue sarcoma that had failed first line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…These findings support the notion that the serial transplantation of PDX models may enhance drug sensitivity, which in turn may contribute to the observations of variable clinical responses. Because of proven discrepancies in drug sensitivity in later passage PDXs, subsequent studies have modified the experimental design to use early passage PDX models . A recent study in head and neck squamous cell carcinoma showed genomic SMAD family member 4 (SMAD4) alterations in PDX .…”
Section: Aggressive Phenotypes and Variable Drug Sensitivitymentioning
confidence: 99%
“…These findings support the notion that the serial transplantation of PDX models may enhance drug sensitivity, which in turn may contribute to the observations of variable clinical responses. Because of proven discrepancies in drug sensitivity in later passage PDXs, subsequent studies have modified the experimental design to use early passage PDX models . A recent study in head and neck squamous cell carcinoma showed genomic SMAD family member 4 (SMAD4) alterations in PDX .…”
Section: Aggressive Phenotypes and Variable Drug Sensitivitymentioning
confidence: 99%
“…With the advances in genetic testing, whole exome sequencing (WES) of fresh tumor specimens via a bioinformatics pipeline may help identify potential actionable chemotherapy agents for angiosarcomas and may lead to developing personalized cancer therapy in the future. A pilot, prospective, nonrandomized control experimental study by Calvert et al analyzed 12 patients with metastatic bone or soft tissue sarcoma who had failed first-line chemotherapy treatment [ 49 ]. One part of the surgical tumor biopsy material was used for WES, and the remaining part was implanted subcutaneously in immunodeficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, WES identified potential actionable therapeutics in all 12 patients with successfully established PDX tumor models in 7 patients. Significant variation in predicted therapeutics was demonstrated between three PDX samples and their matched tumor samples [ 49 ]. This trial is an example of a bright glimpse into modern personalized cancer management as genetic testing gets more available every year [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, current OS therapeutic agents have been limited to cytotoxic drugs interfering with DNA replication (Lamplot et al, 2013; S. Y. Wang, Hu, Qing, Zhang, & Shao, 2020), with a lack of targeted therapies, due to the fact that OSs can have unique underlying genetic drivers in addition to their near‐ubiquitous disruption of the TP53 and Rb tumour suppressors, resulting in their varied protein expression patterns (Krzyszczyk et al, 2018). Personalised medicine approaches have developed using whole exome or genome sequencing to identify targetable drivers including tyrosine kinases that can be involved in OS progression (Calvert et al, 2018). Our current knowledge of the molecular mechanisms and pathways involved in OS progression have the potential to uncover novel therapeutics for OS by targeted small molecule anticancer drugs.…”
Section: Molecular Pathology Of Osmentioning
confidence: 99%